Are these texts readable? An Analysis on the Readability Level of English Textbooks for Indonesian High Schools - Fahrisky Azima; Maria Teodora Ping; A.K. Amarullah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Reading texts or passages from textbooks are commonly used as learning materials in the Indonesian EFL context. This leads to the emergence of readability or reading level analyses for EFL reading materials using conventional formulas which, unfortunately, were originally developed for either English as L1 or L2 context. Moreover, there are alternative readability formulas for EFL materials that are relatively newer yet still underused in the field. Hence, this current descriptive study aimed to address this gap by attempting to analyze the reading texts in three Senior High School English textbook series published by the Ministry of Education and Culture, using formulas measuring the readability level without grade-levelling and using simplified EFL reading materials. In this study, the two specific formulas employed to conduct the readability level analysis were Miyazaki EFL Readability Index and McAlpine EFLAW formula. The results showed that the overall Miyazaki EFL readability score of all reading texts in the 10th, 11th, 12th grade English textbooks was 50, categorized as having a â€œstandardâ€ difficulty. Meanwhile, based on the analysis using McAlpine EFLAW readability formula, the overall readability score was 20.86, which was considered as â€œvery easy to understandâ€. Eventually, it could be concluded that the two formulas could be conveniently used to analyze the readability level of all the reading texts in the textbook series. Moreover, the texts could be deemed as of â€œsuitable and understandableâ€ level for the intended EFL students in Indonesia. Keywords:Readability; Texts; Textbooks; Miyazaki EFL formula; McAlpine EFLAW formula